2017
DOI: 10.1007/s10439-017-1921-6
|View full text |Cite
|
Sign up to set email alerts
|

Ranges of Injury Risk Associated with Impact from Unmanned Aircraft Systems

Abstract: Regulations have allowed for increased unmanned aircraft systems (UAS) operations over the last decade, yet operations over people are still not permitted. The objective of this study was to estimate the range of injury risks to humans due to UAS impact. Three commercially-available UAS models that varied in mass (1.2–11 kg) were evaluated to estimate the range of risk associated with UAS-human interaction. Live flight and falling impact tests were conducted using an instrumented Hybrid III test dummy. On aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…10 Specifically, flight over people is still explicitly prohibited. 10 , 11 We urge the FAA to educate civilians about the dangers inherent in drone flight.…”
Section: Discussionmentioning
confidence: 99%
“…10 Specifically, flight over people is still explicitly prohibited. 10 , 11 We urge the FAA to educate civilians about the dangers inherent in drone flight.…”
Section: Discussionmentioning
confidence: 99%
“…The research group employed both numerical analysis and experimental techniques to determine impact severity on the human body due to UAS collision at various impact conditions. In addition, a biomedical research team at Virginia Polytechnic institute and State University (Virginia Tech) 16 investigated injury risk to human due to UAS collision by using live flight test and drop impact test on a human dummy. Regarding UAS collision impact on aircraft, an analysis model of UAS ingestion into high-bypass engines was developed by Crash Lab at Virginia Tech 17,18 ; the results showed that UAS can pose a serious threat to commercial aircraft jet engines.…”
Section: B Consequence Of Uas Collisionmentioning
confidence: 99%
“…Identification of collision consequence of UAS collision is done based on literature 15,16,19,36,37 on UAS collision analysis and the important findings are presented in this section. This literature addresses the collision effect on a general aviation aircraft, commercial aircraft, and human, inflicted by different UAS types with various weights, using both crash modeling and experimentation.…”
Section: Collision Consequence Analysismentioning
confidence: 99%
“…the Hybrid III crash dummy, is widely used as a representative substitution of a real human body. Campolettano [1] performed a series of live flight test and impact drop test using three different UAS weight classes on an instrumented Hybrid III. The Alliance of System Safety of UAS through Research Excellence (ASSURE) research group also conducted a series of controlled impact drop test using DJI Phantom III UAS on the Hybrid III crash dummy at various UAS impact attitudes and speeds [2][3][4].…”
Section: Introductionmentioning
confidence: 99%